Primary cilia prevent activation of the cGAS-STING pathway during mouse decidualization - Bo Li; Yu-Ying He; Wen-Xu Yao; Dan-Dan Jin; Hui-Na Luo; Meng-Yuan Li; Ying Wu; Zeng-Ming Yang (Communications Biology)
Abstract Primary cilia are antenna-like organelles that sense extracellular signals and function as signaling hubs essential for vertebrate development and homeostasis. Decidualization is crucial for pregnancy establishment and maintenance in both humans and mice. While primary cilia are present in endometrial stromal cells, their role in pregnancy remains unknown. Here, we identify TMEM67, a key component of the ciliary transition zone, as a critical regulator of mouse decidualization. Loss of primary cilia triggers RhoA-MLC2-dependent actomyosin contraction, which transmits mechanical forces to the nuclear lamina, leading to micronuclei formation. Within these micronuclei, double-stranded DNA (dsDNA) can directly bind to cyclic GMP-AMP synthase (cGAS) in situ, initiating downstream signaling. This activation of the cGAS-STING pathway reduces CCL6 production and impairs decidualization. Furthermore, pharmacological inhibition of actin polymerization or RhoA-ROCK signaling alleviates mechanical forces surrounding stromal cells, restores ciliogenesis, maintains nuclear integrity, suppresses the cGAS-STING pathway activation, and ultimately rescues decidualization. Our findings reveal a previously unrecognized mechanism by which primary cilia regulate the actin cytoskeleton to maintain nuclear integrity and prevent DNA leakage. This safeguards against aberrant activation of the cGAS-STING pathway, which would otherwise trigger detrimental immune signaling and impair decidualization.